An Analysis of the Genomic Variability of the Phytopathogenic Mollicute Spiroplasma kunkelii - Carpane, Pablo (2013)
Corn stunt disease has become a factor limiting maize production in some areas of the Americas in recent years. Although resistant maize genotypes have been developed in the past, this resistance has been unstable over time or in some geographical locations. To better understand disease components that could affect the stability of host resistance, we assessed the genome variability of the etiologic agent, Spiroplasma kunkelii. Isolates were obtained from a number of areas, and characterized molecularly by amplification of several regions of the spiroplasma chromosome and sequencing of specific gene fragments. The degree of polymorphism between isolates of different geographic origins was low, and the level of genomic variability was similar within isolates of different countries. Polymorphism among isolates was found in viral insertions and in the sequence of Skarp, a gene that encodes a membrane protein implicated in attachment to insect cells. The results suggest that the genome composition of this species is highly conserved among isolates. Hence, it is unlikely that the instability of maize resistance is due to generation of new pathotypes of S. kunkelii. Instead, other components of this complex pathosystem could account for the breakdown of resistance.